“An infinite approximation, as is the approximation of the square to the circle”. Hölderlin on the problem of the ideal - Silva, Fernando (Revista de Filosofía, 2022)
Amid a period of isolation and profound internal conflict, both in his life and in his thought, arises that which, according to Hölderlin, is “the general conflict in the human being”, namely the conflict between the “aspiration to limitation” and “the aspiration to the absolute”. The aim of this article is to analyze and, as much as possible, follow to its fullest extent, this fundamental thought: to see how it molds Hölderlin’s positions on existence and philosophy, how it meets the most poignant philosophical concerns of the time and hence directly influences Hölderlin’s reading of Fichte, and how it leads the young poet to the notion of an infinite progression of philosophy, that is, to an infinite approximation to the ideal of knowledge.